The Elements of Causal Factors Affecting Customer’s Satisfaction at Hotels and Resorts - Moonsri, Kristiya; Moonsri, Piyarut (Asian Interdisciplinary and Sustainability Review, 2019)
The purposes of this research were: 1) to examine the levels of the customers’ service satisfaction of hotel and resort personnel 2) to analyze the elements of service and professional skills of the hotel and resort personnel that affect customers’ Satisfaction 3) to find out the relationship between service and professional skills of hotel and resort personnel that affect customers’ satisfaction. The samples used in this study were 400 customers who stayed at the hotels and resorts in Khaokho district of Phetchabun province. The tool employed to collect the data was a five-rating-scale questionnaire. The statistics used to analyze the data featured percentage, mean, standard deviation, pearson correlation coefficient, and exploratory factor analysis (EFA). The result showed that the levels of the customers’ service satisfaction of hotel and resort personnel is ranked as highest ( x = 4.51), the aspect that contains the highest mean lies with the issue of service ( x = 4.60), whereas the lowest mean concerns the aspect of professional skills ( x =4.43). The service has the relationships between fifteen variables with the standardized factor loadings of 0.584 to 0.871. The professional skills has the relationships between seven variables with the standardized factor loadings of 0.609 to 0.893. The eigen value is 4.566 and the cumulative % of variance = 65.223. The results show a positive correlation between service and professional skills as .669, with a statistic significance value of 0.01.